New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia) - Tan, Ming Kai; Rahmadi, Cahyo; Robillard, Tony (Zootaxa, 2021)
The genus Phaloria belongs to the monophyletic cricket subfamily Phaloriinae. It is s speciose group comprising 68 species found across Southeast Asia and New Guinea and Australia. The numerical diversity of Phaloria in New Guinea is impressive, but more species still await discovery owing to the large size and remoteness of the island. Based on new material collected from Lobo and Kumawa in West Papua (Indonesia), we describe six new species: Phaloria dischidia Tan & Robillard, sp. nov. from Lobo; Phaloria paradischidia Tan & Robillard, sp. nov. from Kumawa; Phaloria tukul Tan & Robillard, sp. nov. from Lobo; Phaloria brevis Tan & Robillard, sp. nov. from Kumawa; Phaloria berbeda Tan & Robillard, sp. nov. from Lobo; Phaloria lobulata Tan & Robillard, sp. nov. from Kumawa. We also record new localities for a species widespread in Lobo and Kumawa: Phaloria nr. aspersa Gorochov, 1996.